2018
DOI: 10.4269/ajtmh.18-0538
|View full text |Cite
|
Sign up to set email alerts
|

Whatman Protein Saver Cards for Storage and Detection of Parasitic Enteropathogens

Abstract: Current methods to identify the etiology of diarrhea require laboratory facilities for storage of pathogens, which is often challenging in low-resource settings. This study evaluated the efficacy of a low-cost method for preserving stool specimens for the detection of parasitic enteropathogens using Whatman 903 protein saver cards (Sigma-Aldrich, St. Louis, MO). Stool samples known to be positive by multiplex real-time polymerase chain reaction for Giardia lamblia, Cryptosporidium spp., and Entamoeba histolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…This tool has been also assessed for the molecular detection of gastrointestinal parasites (e.g., the coccidian Cryptosporidium spp. and Cyclospora cayetanensis , the flagellated G. duodenalis , and the microsporidia Encephalitozoon intestinalis ) in matrices including clinical specimens and fresh produce [ 16 , 17 , 18 ]. In a seminal study, FTA ® card templates prepared from purified Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tool has been also assessed for the molecular detection of gastrointestinal parasites (e.g., the coccidian Cryptosporidium spp. and Cyclospora cayetanensis , the flagellated G. duodenalis , and the microsporidia Encephalitozoon intestinalis ) in matrices including clinical specimens and fresh produce [ 16 , 17 , 18 ]. In a seminal study, FTA ® card templates prepared from purified Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Whatman ® cards have been proven useful for the diagnosis of pathogenic blood parasites, including canine microfilariae [ 14 ] and malaria-causing Plasmodium species [ 15 ]. However, very few studies have attempted to evaluate their efficacy for the detection of enteric pathogens in stool samples [ 16 , 17 , 18 ]. The protozoan enteroparasites, Giardia duodenalis (syn.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in Bangladesh, similarly good results were shown for the preservation of DNA of protozoan pathogens on Whatman 903 protein saver cards (Sigma‐Aldrich, St. Louis, MO) in a real‐life diagnostic setting (Natarajan et al . 2018). A long‐term assessment confirmed stability of bacterial DNA on Whatman FTA papers stored at ambient temperature in a British laboratory for three years under experimental conditions (Rajendram et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although the first nucleic acid isolation was achieved 150 years ago, there is no general Gold-Standard for downstream applications. Chelex-100 resin has been used since the '90s for diagnostic (Noh et al 2019;, Chen et al 1991) and other purposes (Gill et al 1992) given that it is a rapid, easily performed, and non-expensive method from a variety of biological samples such as semen, blood, tissues, and milk among others, with different sensitivities depending on the pathogen (Natarajan et al 2018).…”
Section: Introductionmentioning
confidence: 99%